Afatinib and Erlotinib in the treatment of squamous-cell lung cancer. (12th December 2018) - Tagliamento, Marco; Genova, Carlo; Rijavec, Erika; Rossi, Giovanni; Biello, Federica; Dal Bello, Maria Giovanna; Alama, Angela; Coco, Simona; Boccardo, Simona; Grossi, Francesco
ABSTRACT: Introduction: Squamous-cell carcinoma (SCC) of the lung represents around 20% of non-small cell lung cancers. Although activating mutations of EGFR are rare in this subtype, its overexpression occurs in more than half the cases. Consequently, many epidermal growth factor receptor (EGFR)-targeted agents have been investigated in patients with SCC. Areas covered: This review summarizes the potential roles of erlotinib and afatinib in SCC of the lung. The authors explore the rationale of targeting EGFR in SCC and the pharmacological properties of erlotinib and afatinib. Subsequently, they describe the most relevant clinical data involving each agent with regard to their safety profile and antineoplastic activity. Particular focus is given to the LUX-Lung 8 trial, which compared erlotinib and afatinib as a second-line treatment in a population of patients affected by advanced SCC of the lung. Expert opinion: Despite being overcome by new therapeutic strategies – in particular immune checkpoint inhibitors – afatinib and erlotinib still represent potential treatment options down the line in lung SCC because they have a more manageable toxicity profile compared to chemotherapy.